FILM AS A PROPAGANDA TOOL: USA AND USSR DURING THE COLD WAR - Radulović, Tijana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
Between 1947 and 1989, disparate political regimes of the USA and the USSR had actively used films to propagate their ideologies. The aim of this article is to identify differences in their propaganda and to answer the following research questions: How did the USA and the USSR use films as an instrument of political propaganda during the Cold War? When it comes to the placement of the messages in films, is there a difference between propaganda actions of the two states? Theoretical review of the Cold War artistic production, as well the content description of the six analysed movies, have shown that the propaganda aims of the two regimes have been equivalent, but that there are certain discrepancies in the propaganda methods. The difference can be observed in the objects of negative propaganda, as well as in a portraying of the enemy and treatment of women. Far less contrast can be found in the so-called “positive campaigns“. Moreover, both sides endeavoured to indicate the “emancipatory“ sides of their own military interventions. In the analysed pro-militaristic films, the American production went one step further, by deprecating the American society which discarded its own war heroes and by agitating the future soldiers. These differences are a consequence of numerous factors, and the recognition of these factors provides us with insight into dominant social and normative currents and conflicts of the Cold War.
Keywords: propaganda; FILMS; cinematography; cold war; USA; USSR